Mandelstam-leibbrandt: Not really a prescription in the light-cone gauge - Bentín, Ricardo; Suzuki, Alfredo T. [UNESP] (World Scientific Publishing, 2007)
Since the very beginning of it, perhaps the subtlest of all gauges is the light-cone gauge, for its implementation leads to characteristic singularities that require some kind of special prescription to handle them in a. proper and consistent manner. The best known of these prescriptions is the Mandelstam-Leibbrandt one. In this work we revisit it showing that its status as a mere prescription is not appropriate but rather that its origin can be traced back to fundamental physical properties such as causality and covariantization methods. © World Scientific Publishing Company.
Keywords: Light-cone gauge; Mandelstam-Leibbrandt prescription